Management of the Symptoms of Metastatic Lung Cancer with Ayurveda (AYUSHDHARA, 2025)
Lung cancer is a leading cause of cancer-related mortality worldwide, with significant challenges in management, especially when complicated by brain metastasis. This case study examines the impact of an integrative approach combining conventional cancer treatments and Ayurvedic therapies on a 45-year-old male diagnosed with metastatic lung cancer and multiple brain metastases. The patient, presenting with symptoms including movement difficulties, cough, swallowing difficulties, swelling and breathlessness, pursued consultation at Shuddhi Ayurveda Panchakarma Hospital, Navi Mumbai. He had undergone standard palliative care, including whole-brain radiotherapy. Despite initial deterioration, the addition of Ayurvedic treatments showed significant improvements. Within months, the patient experienced relief from key symptoms, including a management of swelling in hands and foot and breathlessness, and regained physical independence. Imaging studies revealed marked regression in the size and metabolic activity of both lung and brain lesions decreased significantly. This case highlights the potential of Ayurvedic treatments, such as Ayurvedic interventions and tailored diet, in alleviating symptoms and improving quality of life for patients with advanced lung cancer.